2019
DOI: 10.1111/ggr.12279
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Challenges Associated with the Analysis of Nacre by Atom Probe Tomography

Abstract: In this study atom probe tomography was used to study nacre, an important biocomposite material that is challenging to prepare and analyse by atom probe and, when successful, yields data that is challenging to interpret. It was found that these challenges mainly arise from the insulating and heterogeneous nano‐scale properties of nacre. We outline our current best practice for preparing and running atom probe tips, such as using a low acceleration voltage (< 3 kV) and current (≤ 50 pA) to avoid damage to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…2017, Eder et al . 2019). As PiFM imaging is performed at ambient conditions, materials that are unstable in vacuum can be analysed and experiments can be performed immediately after sample mounting.…”
Section: Fundamentals Of Photo‐induced Force Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…2017, Eder et al . 2019). As PiFM imaging is performed at ambient conditions, materials that are unstable in vacuum can be analysed and experiments can be performed immediately after sample mounting.…”
Section: Fundamentals Of Photo‐induced Force Microscopymentioning
confidence: 99%
“…One of the challenges for unravelling the detailed mechanisms of their formation is associated with the nature of this material, which is electron‐beam‐sensitive, insulating, delicate and hydrous (Eder et al . 2019).…”
Section: Pifm Imaging In Geochemistry and Environmental Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eder et al . () detail their successful method for analysis of nacre (the iridescent material commonly known as mother‐of‐pearl) by atom probe tomography to overcome challenges mainly caused by nano‐scale heterogeneities, related to sample preparation, analysis and data interpretation. Wang et al .…”
mentioning
confidence: 99%
“…They showed that a modified grinding technique allowed reliable results to be obtained for small test portion masses. Eder et al (2019) detail their successful method for analysis of nacre (the iridescent material commonly known as mother-of-pearl) by atom probe tomography to overcome challenges mainly caused by nano-scale heterogeneities, related to sample preparation, analysis and data interpretation. Wang et al (2019) detail their improved procedure for analysis of Os isotope ratios from exceedingly small samples, using new 10 13 Ω pre-amplifier technology in TIMS, and applied their procedure to geological RMs with low Os mass fractions.…”
mentioning
confidence: 99%